The bee genus Colletes Latreille 1802 in Ethiopia (Hymenoptera: Apoidea: Colletidae) - Kuhlmann, Michael; Pauly, Alain (Zootaxa, 2013)
The Ethiopian species of the bee genus Colletes are revised and redescribed to facilitate their identification and future research. Colletes langano Kuhlmann sp. n., C. aethiopicus Kuhlmann sp. n. and C. senkelensis Kuhlmann sp. n. are described as new. The females of C. abessinicus Friese 1915 and C. microdontus Cockerell 1937 and the males of C. rothschildi Vachal 1909 and C. somereni Cockerell 1947 are described for the first time. Colletes rufitarsis Friese 1909 is removed from the list of Ethiopian species so currently a total of eight Colletes species are known from this country. A key is provided to facilitate species identification.